EFFECT OF RETURN ON ASSETS, RETURN ON EQUITYAND RETURN ON INVESTMENT ON COMPANY VALUE (Manufacturing Companies In The Consumer Goods Industry Sector Listed On Idx 2016-2020) - Aliyyatus Sa'adah; Andi Farouq Hasan; Luluk Nur Azizah (Sean Institute, 2023)
This study aims to determine the effect of return on assets, return on equity and return on investment on the value of consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2020. This study used a sample of companies that became the research sample, namely as many as 45 companies. This study uses secondary data obtained from the financial statements of manufacturing companies listed on the IDX in the 2016-2020 period. Data processing using SPSS version 25. The data analysis method used descriptive statistics, classical assumption test, multiple linear regression, and hypothesis testing. The results of this study indicate that the ratio of ROA, ROE, and ROI partially and simultaneously has a significant effect on firm value.